Oil sands operations as a large source of secondary organic aerosols - Liggio, John; Li, Shao-Meng; Hayden, Katherine; Taha, Youssef M.; Stroud, Craig; Darlington, Andrea; Drollette, Brian D.; Gordon, Mark; Lee, Patrick; Liu, Peter; Leithead, Amy; Moussa, Samar G.; et al. (NATURE, 2016)
Worldwide heavy oil and bitumen deposits amount to 9 trillion barrels of oil distributed in over 280 basins around the world(1), with Canada home to oil sands deposits of 1.7 trillion barrels(2). The global development of this resource and the increase in oil production from oil sands has caused environmental concerns over the presence of toxic compounds in nearby ecosystems(3,4) and acid deposition(5,6). The contribution of oil sands exploration to secondary organic aerosol formation, an important component of atmospheric particulate matter that affects air quality and climate(7), remains poorly understood. Here we use data from airborne measurements over the Canadian oil sands, laboratory experiments and a box-model study to provide a quantitative assessment of the magnitude of secondary organic aerosol production from oil sands emissions. We find that the evaporation and atmospheric oxidation of low-volatility organic vapours from the mined oil sands material is directly responsible for the majority of the observed secondary organic aerosol mass. The resultant production rates of 45-84 tonnes per day make the oil sands one of the largest sources of anthropogenic secondary organic aerosols in North America. Heavy oil and bitumen account for over ten per cent of global oil production today(8), and this figure continues to grow(9). Our findings suggest that the production of the more viscous crude oils could be a large source of secondary organic aerosols in many production and refining regions worldwide, and that such production should be considered when assessing the environmental impacts of current and planned bitumen and heavy oil extraction projects globally.